Integrasi Nilai-nilai Karakter dalam Pembelajaran Fikih di Madrasah Ibtidaiyah - Lilik Farida (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to examine how the process of integrating character values in Islamic Jurisprudence learning at MI Az-Zainiyah III Probolinggo and identify the factors that influence it. The approach used is descriptive qualitative, with six research subjects, consisting of the head of the madrasah, the vice head of the madrasah for curriculum, the Islamic Jurisprudence subject teacher, and three students from grade IV totaling 26 students. Data collection techniques were carried out through interviews, observations, and documentation. The results of the study indicate that the integration of character values in Islamic Jurisprudence learning is carried out through two main stages, namely planning and implementing learning. At the planning stage, the teacher has included character values in the Learning Implementation Plan (RPP) as part of the learning objectives. While in its implementation, internalization of character values is carried out in stages starting from the opening, core, to closing activities of learning, with the aim of forming the character of students. The teacher also provides stimulus in the form of interactions that support character formation during the learning process. In its implementation, the teacher uses various methods such as lectures, discussions, demonstrations, and questions and answers, and applies a scientific approach to encourage student activity, so that character values can be more easily embedded. The factors that influence the integration of character values are divided into two, namely supporting and inhibiting factors. Supporting factors include madrasah activities that support character formation and a conducive school environment. Meanwhile, inhibiting factors include limited learning time, diverse student backgrounds, and readiness in learning planning.